Epidemiology and molecular analyses of respiratory syncytial virus in the 2021–2022 season in northern Italy - Lai, Alessia; Bergna, Annalisa; Fabiano, Valentina; Ventura, Carla della; Fumagalli, Giulia; Mari, Alessandra; Loiodice, Martina; Zuccotti, Gian Vincenzo; Zehender, Gianguglielmo (Frontiers in Microbiology, 2024)
Background: Human respiratory syncytial virus (RSV) is the leading cause of acute lower respiratory tract infection among infants and young children worldwide, with seasonal peaks in January/February. The aim of this study was to characterize the RSV samples from a pediatric cohort in the 2021-2022 season in Italy. Methods: 104 samples were collected from pediatric patients attending the "Vittore Buzzi" Children's Hospital in Milan in the 2021-2022 season. RT-PCR and Next Generation Sequencing were used to discriminate subgroups and obtain whole genomes. Maximum-Likelihood and Bayesian phylogenetic methods were used to analysed Italian sequences in the European contest and dated Italian clusters. Results: The median age was 78 days and 76.9% of subjects required hospitalization, with a higher proportion in patients aged <3 months. An equal proportion of subgroups A (GA2.3.5) and B (GB5.0.5a) was found, with significant differences in length of hospitalization, days of supplemental oxygen treatment and intravenous hydration duration. Phylogeny highlighted 26 and 37 clusters containing quite the totally of Italian sequences for RSV-A and B, respectively. Clusters presented a tMRCA between 12/2011-02/2017 and 05/2014-12/2016 for A and for B subgroup, respectively. Compared to European sequences, specific mutations were observed in Italian strains. Conclusions: These data confirmed a more severe clinical course of RSV-A, particularly in young children. This study permitted the characterization of recent Italian RSV whole genomes highlighting the peculiar pattern of mutations that needs to be more investigated and monitored.